[N-Methyl-2-pyrrolidone][C1–C4 carboxylic acid]: a novel solvent system with exceptional lignin solubility. Issue 70 (29th July 2015) - Mu, Liwen; Shi, Yijun; Chen, Long; Ji, Tuo; Yuan, Ruixia; Wang, Huaiyuan; Zhu, Jiahua
Abstract : Novel solvent systems composed of N -methyl-2-pyrrolidone and carboxylic acid outperform the conventional solvents and ionic liquids in lignin dissolution capability. Abstract : Novel solvent systems composed of N -methyl-2-pyrrolidone and C1–C4 carboxylic acid exhibit unique physicochemical properties, e.g. large polarity, low viscosity and excellent hydrogen bonding capacity, which have demonstrated excellent lignin solubility that outperforms conventional solvents and ionic liquids.